THE EFFECTIVENESS OF APPAREL PATTERN DRAFTING IN MANUAL SYSTEM FOR TVET FASHION PROGRAM - Norulaini Mohd Ramly , Nazlina Shaari (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Clothing pattern design is one of the most important components of clothing production from the past to the present. Technological advances in the production of clothing patterns are growing rapidly. The use of computer-aided design (CAD) is very popular in developed nations. Many skill-based educational institutions in Malaysia also use manual systems for TVET fashion programmes. It is also important that the use of a hands-on manual system ensures that students have skills and adepts. This is because the manual system is easier to use and saves costs while improving students ' understanding and mastery. Students can understand and apply directly on the go, without the need to use computer application software. The objectives of this study were the use of literature review methods, research knowledge and experience, questionnaires and visual representations of clothing pattern production using a manual system. The methods of research used are observations and interviews with users and design experts to find out the effectiveness of a manual system that is still applicable to skill-based education. The results of this research have shown that the use of the manual method for designing clothing patterns is particularly important for new users. Furthermore, before learning how to create clothing patterns using CAD system software applications, users need to understand the manual method for producing patterns.